Ligand-Free Signaling of G-Protein-Coupled Receptors: Relevance to μ Opioid Receptors in Analgesia and Addiction - Wolfgang Sadee; John C. McKew (Molecules, 2022)
Numerous G-protein-coupled receptors (GPCRs) display ligand-free basal signaling with potential physiological functions, a target in drug development. As an example, the μ opioid receptor (MOR) signals in ligand-free form (MOR-μ*), influencing opioid responses. In addition, agonists bind to MOR but can dissociate upon MOR activation, with ligand-free MOR-μ* carrying out signaling. Opioid pain therapy is effective but incurs adverse effects (ADRs) and risk of opioid use disorder (OUD). Sustained opioid agonist exposure increases persistent basal MOR-μ* activity, which could be a driving force for OUD and ADRs. Antagonists competitively prevent resting MOR (MOR-μ) activation to MOR-μ*, while common antagonists, such as naloxone and naltrexone, also bind to and block ligand-free MOR-μ*, acting as potent inverse agonists. A neutral antagonist, 6β-naltrexol (6BN), binds to but does not block MOR-μ*, preventing MOR-μ activation only competitively with reduced potency. We hypothesize that 6BN gradually accelerates MOR-μ* reversal to resting-state MOR-μ. Thus, 6BN potently prevents opioid dependence in rodents, at doses well below those blocking antinociception or causing withdrawal. Acting as a ‘retrograde addiction modulator’, 6BN could represent a novel class of therapeutics for OUD. Further studies need to address regulation of MOR-μ* and, more broadly, the physiological and pharmacological significance of ligand-free signaling in GPCRs.